Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0108-001 4, Aberdare Gardens, Hampstead, LONDON, N.W.6, 19th October, 1937. Mrs. B. Church, 346A. Kings Road, Paulton Square, CHELSEA, S.W.3. Dear Mrs. Church, Thank you very much for your letter of October 16th, and I shall read your letter to the Committee at its next meeting. Yours sincerely, 292C/946/2/108